Dose to medium in head and neck radiotherapy: Clinical implications for target volume metrics - Hardcastle, Nicholas (Phys Imaging Radiat Oncol, 2019)
BACKGROUND AND PURPOSE: In radiotherapy dose calculation, advanced type-B dose calculation algorithms can calculate dose to medium (D(m)), as opposed to Type-B algorithms which compute dose to varying densities of water (D(w)). We investigate the impact of D(m) on calculated dose and target coverage metrics in head and neck cancer patients. METHODS AND MATERIALS: We reviewed 27 successfully treated (disease free at two-years post-(chemo)radiotherapy) human papillomavirus-associated (HPV) oropharyngeal cancer (ONC) patients treated with IMRT. Doses were calculated with Type-B and Linear Boltzman Transport Equation (LBTE) algorithms in a commercial treatment planning system, with the treated multi-leaf collimator patterns and monitor units. Coverage for primary Gross Tumour Volume (GTVp), high dose Planning Target Volume (PTV) (PTV_High), mandible within PTV_High (Mand ∩ PTV) and PTV_High excluding bone (PTV-bone) were compared between the algorithms. RESULTS: Dose to 95% of PTV_High with LBTE was on average 1.1 Gy/1.7% lower than with Type-B (95%CI 1.5–1.9%, p < 0.0001). This magnitude was inversely linearly correlated with the relative volume of the PTV_High containing bone (pearson r = −0.81). Dose to 98% of the GTVp was 0.9 Gy/1.3% lower with LBTE compared with Type-B (95%CI 1.1–1.5%, p < 0.05). Dose to 98% of Mand ∩ PTV was on average 3.4 Gy/5.0% lower with LBTE than with Type-B (95%CI 4.6–5.4%, p < 0.0001). CONCLUSION: In OPC treated with IMRT, D(m) results in significant reductions in dose to bone in high dose PTVs. Reported GTVp dose was reduced, but by a lower magnitude. Reduced coverage metrics should be expected for OPC patients treated with IMRT, with dose reductions limited to regions of bone.